Recovery from Resistance Exercise in Older Adults: A Systematic Scoping Review - Eleanor Jayne Hayes; Emma Stevenson; Avan Aihie Sayer; Antoneta Granic; Christopher Hurst (SpringerOpen, 2023)
Abstract Background Resistance exercise is recommended for maintaining muscle mass and strength in older adults. However, little is known about exercise-induced muscle damage and recovery from resistance exercise in older adults. This may have implications for exercise prescription. This scoping review aimed to identify and provide a broad overview of the available literature, examine how this research has been conducted, and identify current knowledge gaps relating to exercise-induced muscle damage and recovery from resistance exercise in older adults. Methods Studies were included if they included older adults aged 65 years and over, and reported any markers of exercise-induced muscle damage after performing a bout of resistance exercise. The following electronic databases were searched using a combination of MeSH terms and free text: MEDLINE, Scopus, Embase, SPORTDiscus and Web of Science. Additionally, reference lists of identified articles were screened for eligible studies. Data were extracted from eligible studies using a standardised form. Studies were collated and are reported by emergent theme or outcomes. Results A total of 10,976 possible articles were identified and 27 original research articles were included. Findings are reported by theme; sex differences in recovery from resistance exercise, symptoms of exercise-induced muscle damage, and biological markers of muscle damage. Conclusions Despite the volume of available data, there is considerable variability in study protocols and inconsistency in findings reported. Across all measures of exercise-induced muscle damage, data in women are lacking when compared to males, and rectifying this discrepancy should be a focus of future studies. Current available data make it challenging to provide clear recommendations to those prescribing resistance exercise for older people.